Synthesis of Mxene-PVDF composite nanofiber cloth - Sounderajan, Sugaseni; Ling, Jin Kiong; Jose, Rajan (Penerbit Universiti Malaysia Pahang, 2022)
Electrospinning is a versatile and low-cost technology in producing polymer fibers with diameter ranging from a few microns to nanometers, which can be suitably twisted to make yarns. The aim of this research is to synthesize MXENE-incorporated poly(vinylidene fluoride) (MXENE@PVDF) nanofiber using electrospinning method. The effect of MXENE-to-PVDF ratio on the properties of the nanofiber is studied to investigate its suitability as the separator for energy storage devices. The formation of MXENE@PVDF nanofibers through electrospinning method was confirmed through Field-Emission Scanning Electron Microscope (FESEM). X-ray powder diffraction spectroscopy (XRD) was utilized to study the sample crystallinity and to confirm presence of MXENE. The presence of MXENE was further validated through observing the interaction of functional group between MXENE and PVDF through Fourier-transform infrared spectroscopy (FTIR). The main purpose of this project is to formulate a polymeric solution using MXENE and PVDF with desirable rheological properties such that a polymeric mat can be synthesized using electrospinning.